Letter - Conley, Andrew
028-0077-001 TELEGRAMS: AMALGAMATE. LEEDS TELEPHONE: LEEDS 20557. NATIONAL UNION OF TAILORS & GARMENT WORKERS. Incorporating the Amalgamated Society of Tailors & Tailoresses, Scottish Operative Tailors & Tailoresses and the Garment Workers Union. HEAD OFFICE: Union Chambers. 20 PARK PLACE LEEDS, 1. General President: G. Rowlerson. General Secretary: A. Conley. Ref. 9/1/6. 23rd January 1937. Mr. H. V. Tewson, Trades Union Congress General Council, Transport House, (South Block), Smith Square, LONDON, S.W.1. Dear Mr. Tewson, Many thanks for your letter of the 21st January, accompanied by cheque for £100, acknowledgment of which is herewith enclosed. We are proceeding with our efforts and will advise you of the results as soon as possible. With best wishes. Yours sincerely, A. Conley General Secretary. 292/946/28/77